The state, venture capital and domestic high-tech start-ups in an late-development economy: Ireland - Frank Barry; Beata Topa (University College Dublin, UCD School of Economics, 2006)
Ireland, the “Celtic Tiger” economy of today, had for decades been one of the poorest of the Western European economies. This paper analyses the three-pronged approach of the Irish authorities in promoting successful high-tech start-up firms. An investment climate conducive to the emergence of such firms was first created. Emerging firms were then offered substantial public support in developing their capabilities. Finally, the authorities played a significant role in promoting the emergence of a dynamic venture capital industry. Such interventionist policies would have been highly unlikely to succeed in the absence of strong institutional capacity.
hdl:10197/1302
Keywords: 330; Venture Capital; High-Tech Start Ups; Ireland